MODAL SOSIAL ORGANISASI PERANTAU SAS (SULIT AIR SEPAKAT) DI KOTA PEKANBARU - Sulastri, Rahmi; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was carried out in the overseas organization SAS (Sulit Air Sepakat) Pekanbaru City. The organization is a sorority  organization origaniting from Nagari Sulit Air X Koto Diatas District Solok Regenncy. This organization from the beginning wa formed until now still persists and exists in Pekanbaru City. The purpose of this research  is to find out how elements of social capital play a role in the existence of  SAS (Sulit Air Sepakat) organization and how rationality become a members in joining the SAS (Sulit Air Sepakat) organization. this research uses descriptive qualitative methods. There were also informants in this study totaling 8 people 3 of whom were supporting informants. In determininhg informants using purposive sampling technique. Data collection techniques namely by observation interview and documentation. The theory used is the social capital theory put forward by Putnam which consistsof 3 elements of social capital, namely networks, trust and norms. The results of this study explain that an organization requires social capital to maintain the relationship and sustainability of the SAS (Sulit Air Sepakat) organization in the City of Pekanbaru. The elements of social capital that play a role in the SAS (Sulit Air Sepakat) organization is trust. This scan be seen from the solidarity of the SAS (Sulit Air Sepakat) organization itself. the cohesiveness between the members, management and the trust given by outsiders to the SAS (Sulit Air Sepakat) organization. The rationality of members in joining the SAS (Sulit Air Sepakat) organization is instumental rationality, value-oriented rasionality and tradisonal rasionality. The rationality is carried out  by the members by considering and taking into account firts before the action is stated.  Keyword:  social capital, rasionality, SAS (Sulit Air Sepakat).